PENGARUH CU TERHADAP REAKSI ANTARMUKA BAJA DAN ALUMINIUM DENGAN PERLAKUAN DIFUSI - Karengke, Mathius; Triyono, Triyono; Supriyanto, Agus (ROTASI, 2014)
Nowadays, developing vehicle is made as light as posible with the purpose to reduce energy consumption. For this reason, material that can be used is aluminium that has light weight and non corrosion properties. Aluminum structure will be not strong enough, it still need another material like steel to make it stronger and stiffer. Joining aluminum to steel has problems because of very low solubility, thus it requires other material as its medium in which it accelerates promoter solubility aluminum to steel. In this study, mixture of Fe and Cu powder was used as promoter material or filler in the process of diffusion welding of aluminium and steel.. TheÂ  good results diffusion between the steel with aluminum filler hence the need for variation of Fe and Cu. Aluminum and steel welding process with adapting diffusion treatment will produces intermetallic layer. Intermetallic layer was formed from the fussion among two different material, and it made new compound. This research showed some different solubility level of aluminum in steel in every variation of filler composition. The highest solubility ratio of aluminum in steel was 0.4 which reached in the specimens with filler composition of 40% Fe,60% Cu and 60% Fe,40% Cu.